Paul and the heritage of Israel: Paul's claim upon Israel's legacy in Luke and Acts in the light of the Pauline letters - Moessner, David P.; Marguerat, Daniel; Parsons, Mikeal Carl; Wolter, Michael (Luke the interpreter of Israel, 2012)
"As a sequel to the hugely successful Jesus and the Heritage of Israel, this book brings together fourteen internationally acclaimed scholars in antiquities studies and experts on Paul and Luke. The contributors provoke new approaches to the troubled relation of the Lukan Paul by re-configuring the figure and impact of Paul upon nascent Christianity, with the two leading questions as a driving force. First, 'Who is "Israel" and the "church" for Luke and Luke's Paul' and secondly 'Who is Jesus of Nazareth and who is Paul in relation to both?' The contributors provide challenging new perspectives on approaches to the figure of Paul in recent scholarship as well as in the scholarship of previous generations, 're-figuring' Paul by examining both how he is portrayed in Acts, and how the Pauline figure of Acts may be envisioned within Paul's own writings. Paul and the Heritage of Israel thus accomplishes what no other single volume has done: combining both the 'Paul of Paul' and the 'Paul of Luke' in one seminal volume."--Bloomsbury Publishing